Effect of Climate Change on Rice Farming and its Coping Strategies - Sapkota, Sudha Nepal; Pandey, Sushil; Regmi, Punya Prasad; Sah, Shrawan Kumar; Tripathi, Bhaba Prasad (Economic Journal of Nepal, 2012)
Rice is staple crop in Nepal and various factors play an important role in the fluctuating production of rice. By assuming the decrease in yield is due to change in various parameters of climate. Winds, droughts, rainfall, hailstones and erosion were the basic climatic factors undertaken for the study. Result depicted that ninety four percent of the respondents reported that they have been facing severe changes in climate as compared to 10 years before. Drought was the major parameter in effect of the rice farming. Rice has been replaced by maize for alternatives. However, the consumption pattern shows 97 percent of peoples prefer to have rice as a major food. Therefore, drought tolerant varieties such as Sukkha-1, Sukkha-2, Sukkha-3, Khumal-10 and Khumal-13 should be introduced in the study areas. Also, SRI (System of Rice Intensification) could be other possibilities to cope with the climate changes. The Economic Journal of Nepal, Vol. 35, No. 1, January-March 2012 (Issue N0. 137)